The central bank as a risk manager: quantifying and forecasting inflation risks - Lutz Kilian; Simone Manganelli (European Central Bank (ECB), 2003)
In deciding the monetary policy stance, central bankers need to evaluate carefully the risks the current economic situation poses to price stability. We propose to regard the central banker as a risk manager who aims to contain inflation within pre-specified bounds. We develop formal tools of risk management that may be used to quantify and forecast the risks of failing to attain that objective. We illustrate the use of these risk measures in practice. First, we show how to construct genuine real time forecasts of year-on-year risks that may be used in policy-making. We demonstrate the usefulness of these risk forecasts in understanding the Fed's decision to tighten monetary policy in 1984, 1988, and 1994. Second, we forecast the risks of worldwide deflation for horizons of up to two years. Although recently fears of worldwide deflation have increased, we find that, as of September 2002, with the exception of Japan there is no evidence of substantial deflation risks. We also put the estimates of deflation risk for the United States, Germany and Japan into historical perspective. We find that only for Japan there is evidence of deflation risks that are unusually high by historical standards.
Keywords: E31; E37; E52; E58; C22; 330; deflation; forecast; inflation; monetary policy; risk